Paritas dan Kehamilan Post Term terhadap Kejadian Asfiksia Neonatorum - Pera Mandasari (LPPM STIKES Al-Ma'arif Baturaja, 2018)
Asphyxia Neonatorum is a condition when a baby con not soon breathe spontaneously. The purpose of this study was to determine the relationship between parity and post-term giving with the incidence of asphyxia neonatorum in the District General Hospital Prabumulih 2017. This study uses Analytical Survey by using a cross-sectional approach. The study population was all infants born in the District General Hospital Prabumulih 2017, amounting to 1.394 people. The number of samples in this study were 310 respondents. The results showed that there was a significant relationship between parity and neonatal asphyxia with a p-value <α 0,000 and there was a significant relationship between post-term pregnancies against neonatal asphyxia with a p-value <0.005. Prenatal care (Antenatal Care) should be done at least four times to be able to detect early the possibility of maternal and neonatal emergencies that can occur during pregnancy until the time of delivery.